Long-term environmental enrichment overcomes depression, learning, and memory impairment in elderly CD-1 mice with maternal sleep deprivation exposure - Zhang, Yue-Ming; Wei, Ru-Meng; Li, Xue-Yan; Feng, Yi-Zhou; Zhang, Kai-Xuan; Ge, Yi-Jun; Kong, Xiao-Yi; Liu, Xue-Chun; Chen, Gui-Hai (Frontiers in Aging Neuroscience, 2023)
Early-life stress disrupts central nervous system development and increases the risk of neuropsychiatric disorder in offspring based on rodent studies. Maternal sleep deprivation (MSD) in rodents has also been associated with depression and cognitive decline in adult offspring. However, it is not known whether these issues persist into old age. Environmental enrichment is a non-pharmacological intervention with proven benefits in improving depression and cognitive impairment; however, it is unclear whether these benefits hold for aging mice following MSD exposure. The aim of this study was to explore the effects of MSD on depression and cognition in elderly offspring CD-1 mice and to determine whether long-term environmental enrichment could alleviate these effects by improving neuroinflammation and synaptic plasticity. The offspring mice subjected to MSD were randomly assigned to either a standard environment or an enriched environment. At 18 months of age, the forced swimming and tail suspension tests were used to evaluated depression-like behaviors, and the Morris water maze test was used to evaluate cognitive function. The expression levels of hippocampal proinflammatory cytokines and synaptic plasticity-associated proteins were also measured. MSD increased depression-like behaviors and impaired cognition function in aging CD-1 offspring mice. These effects were accompanied by upregulated interleukin (IL)-1β, IL-6, and tumor necrosis factor-α expression, and downregulated brain-derived neurotrophic factor, tyrosine kinase receptor B, postsynaptic density-95, and synaptophysin expression in the hippocampus. All of these changes were reversed by long-term exposure to an enriched environment. These findings suggest that MSD exerts long-term effects on the behaviors of offspring in mice, leading to depression and cognitive impairment in older age. Importantly, long-term environmental enrichment could counteract the behavior difficulties induced by MSD through improving hippocampal proinflammatory cytokines and synaptic plasticity-associated proteins.